Attraction and avoidance of wild demersal fish and crustaceans to open-net aquaculture pens resolved by baited and towed underwater camera surveys - Dunlop, Katherine; Strammer, Ilona; Keeley, Nigel (Frontiers in Marine Science, 2024)
Wild gadoids are known to have close associations with open-net fish farms, leading to concerns about changes in natural fish distribution and feeding patterns. However, the nature of the relationships between non-pelagic fish and mobile benthic invertebrates and aquaculture facilities remains poorly documented, even though this group contains widespread commercial North Atlantic species. This study utilizes baited remote and towed underwater video surveys to resolve the ecosystem-level effects of open salmon aquaculture cages and organic enrichment on the spatial structure and relative abundance of demersal fish and crustacean communities. Towed camera surveys were carried out 50 to >600 m downstream of three farms producing finfish in Western Finnmark and four in the Frøya region of Norway. Towed camera surveys were paired with baited remote underwater video surveys at the four Frøya farms. The declining enrichment gradient with distance downstream of the farm cages was confirmed by modeled and observed depositional flux measurements and benthic infaunal community composition. The community structure of wild demersal fish and crustaceans in close association with the seafloor varied with the distance from the aquaculture sites. In addition to the established pattern of the attraction of gadoids, the edible crab (Cancer pagurus) and flatfish (Pleuronectes platessa and Microstomus kitt) showed a preference for areas 10–150 m from farm cages where organically enriched sediments contain a rich food source of opportunistic polychaetes. In contrast, the cuckoo wrasse (Labrus mixtus) and the common hermit crab (Pagurus bernhardus) exhibited higher numbers in locations over 600 m from the farms. Findings show how changes in the benthic food web from aquaculture enrichment can affect the spatial distribution of poorly studied but commercially important fish and crustaceans. Such changes in distribution can impact the availability of these species to coastal fisheries, especially in dense aquaculture regions.